The spike S2 substitution, P804L, drives the adaptation of BANAL-20–236 to a broad range of Rhinolophus bat ACE2 - Chen, Luo; Hinay, Alfredo A.; Fujita, Shigeru; Ito, Jumpei; Asakura, Hiroyuki; Nagashima, Mami; Sadamasu, Kenji; Yoshimura, Kazuhisa; Sato, Kei (Frontiers in Virology, 2025)
Understanding how bat coronaviruses circulate in wildlife, including bats in nature, can help assess the risks of cross-species transmission of potentially pathogenic viruses to humans. However, the evolutionary molecular mechanisms that enable sarbecoviruses to utilize diverse Rhinolophus bat ACE2 receptors remain poorly understood. In this study, we investigate the adaptive potential of BANAL-20–236—a bat sarbecovirus sharing 95.2% amino acid identity with SARS-CoV-2—in overcoming ACE2 compatibility barriers across various Rhinolophus bat species. Comparative replication kinetics revealed that BANAL-20–236 exhibits reduced fitness compared to SARS-CoV-2 in the cells expressing ACE2 from R. ferrumequinum, R. sinicus, and R. shameli. Serial passaging in these cells was selected for the mutants bearing substitutions in the S2 subunit, P804L and S876Y, which enhanced infectivity in R. sinicus and R. shameli ACE2. Both substitutions conferred increased infectivity in the cells expressing a variety of Rhinolophus ACE2. We show that the P804L substitution, located near the S2’ cleavage site, increased viral infectivity in a transmembrane serine protease 2 (TMPRSS2)-independent entry. Conversely, the increased infectivity by the S876Y substitution, which is closed to heptad repeat 1, is dependent on TMPRSS2. Our in vitro cell culture experiments suggest that the S2-driven evolution occurring in nature could facilitate the adaptation of bat coronaviruses to the diverse usage of bat ACE2.